Modulating immune responses for enhanced cell therapies: The dual role of multi-scale biomaterials - Jia'nan Zeng; Yuhong Jin; Yanxiao Ao; Wenjing Li; Kaini Liang; Haoke Chen; Yi Long; Yanan Du (EngMedicine)
The efficacy of cell therapy is compromised by the suboptimal survival and function of transplanted cells, which can be partly attributed to uncontrolled immunomodulation. To address this issue, the dual role of biomaterials in assisting immune activation and evasion can be used to fine-tune immune responses and improve the efficacy and safety of cell therapy. Herein, we summarize different methods used to engineer therapeutic cells with biomaterials across multiple spatial scales and review how biomaterials assist in immune activation or evasion in cell therapy based on a discussion of the effects of biomaterials on endogenous immune cells. We also discuss the appealing features of biomaterials that polarize immune responses toward type 1 or type 2 immunity. In future studies, the biophysical and biochemical properties of biomaterials could be better leveraged for immunomodulatory purposes to fuel prominent improvements in cell therapy, and the relevant regulatory mechanisms should be investigated in a more systematic and in-depth manner.